Curriculum Concepts and Theories from the Perspective of Islamic Education - Nst, Anjar Mahmaudin; Murhayati, Sri; Zaitun, Zaitun (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Islamic education curriculum is a design or study program related to Islamic Religious Education materials or lessons, learning process objectives, methods and approaches and evaluation forms. The research method in this research is library research through collecting data from books and articles related to the Concept and Theory of Islamic Education Curriculum, using descriptive analysis. The curriculum as an educational design, has a central position, determining educational activities and outcomes. Its preparation requires a strong foundation, based on the results of deep thought and research. A weak curriculum will produce weak humans as well. The Islamic education curriculum is Islamic education materials in the form of activities, knowledge and experiences that are deliberately and systematically given to students in order to achieve the goals of Islamic education. The Islamic education curriculum includes three very important issues, namely: the problem of faith (aqidah), the problem of Islam (shari'ah), and the problem of ihsan (morals). The curriculum as an educational design, has a central position, determining educational activities and results. Its preparation requires a strong foundation, based on the results of in-depth thinking and research.